2020
DOI: 10.1074/jbc.ra120.014858
|View full text |Cite
|
Sign up to set email alerts
|

miR-26a mediates LC-PUFA biosynthesis by targeting the Lxrα–Srebp1 pathway in the marine teleost Siganus canaliculatus

Abstract: MicroRNAs (miRNAs) have been recently shown to be important regulators of lipid metabolism. However, the mechanisms of miRNA-mediated regulation of long-chain polyunsaturated fatty acids (LC-PUFA) biosynthesis in vertebrates remain largely unknown. Herein, we for the first time addressed the role of miR-26a in LC-PUFA biosynthesis in the marine rabbitfish Siganus canaliculatus. The results showed that miR-26a was significantly down-regulated in liver of rabbitfish reared in seawater and in S. canaliculatus hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
(95 reference statements)
1
11
0
Order By: Relevance
“…29,32 Furthermore, miR-33 and miR-24 can promote the biosynthesis of LC-PUFA by targeting insulin-induced gene 1 (insig1), thus facilitating the Srebp1 pathway, 31,33 and miR-26a mediates LC-PUFA biosynthesis through the liver X receptor α (Lxrα)-Srebp1 pathway by targeting lxrα. 34 These findings highlight the key roles of miRNAs in the post-transcriptional regulation of the metabolism of essential fatty acids in vertebrates. In the present study, we found that miR-145, like other identified miRNAs, including miR-33 and miR-24, 31,33 also responds to both salinity and availability of C 18 PUFA precursors (e.g.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…29,32 Furthermore, miR-33 and miR-24 can promote the biosynthesis of LC-PUFA by targeting insulin-induced gene 1 (insig1), thus facilitating the Srebp1 pathway, 31,33 and miR-26a mediates LC-PUFA biosynthesis through the liver X receptor α (Lxrα)-Srebp1 pathway by targeting lxrα. 34 These findings highlight the key roles of miRNAs in the post-transcriptional regulation of the metabolism of essential fatty acids in vertebrates. In the present study, we found that miR-145, like other identified miRNAs, including miR-33 and miR-24, 31,33 also responds to both salinity and availability of C 18 PUFA precursors (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, as tissue distribution of miRNAs may partly reflect miRNA functions, 52 we examined the tissue distribution of miR-145 and found that miR-145 was ubiquitously expressed including in liver, while the expression level of hnf4α was relatively highest in intestine, followed by liver. 28 Further in silico analyses found that, among the LC-PUFA biosynthesis related genes, miR-145 potentially targeted the 3′UTR of hnf4α, which is different from other identified miRNAs' target genes, [29][30][31][32][33][34] and in vitro luciferase reporter assays identified hnf4α as a novel target of miR-145 in rabbitfish. Moreover, when knocked down the miR-145, the expression of Hnf4α and LC-PUFA biosynthesis key enzymes were significantly upregulated and subsequently the accumulation of LC-PUFA were increased both in hepatocytes in vitro and in rabbitfish in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations